Assessing the STEM landscape: the current instructional climate survey and the evidence-based instructional practices adoption scale - R. Eric Landrum; Karen Viskupic; Susan E. Shadle; Doug Bullock (SpringerOpen, 2017)
Abstract Background The efficacy of active learning within STEM education is clear, and many institutions are working to help faculty adopt evidence-based instructional practices (EBIPs) which can promote active learning. In order to know the current status of our campus regarding these goals, measures of current instructional climate and the adoption of evidence-based instructional practices (EBIPs) are desired. Results Using a campus-wide online survey approach with remuneration for faculty participants, the 28-item current instructional climate survey (CICS) and the 6-item EBIP adoption scale were developed. When CICS and EBIP adoption scale outcomes are compared, patterns emerge which reflect the climate, conditions, and personal characteristics of faculty at different stages of EBIP adoption. Conclusions Although not causal relationships, understanding both climate and personal change characteristics can be helpful to campus change agents in assessing the current STEM landscape of faculty practices.